1996
DOI: 10.1182/blood.v87.6.2154.bloodjournal8762154
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of thrombopoietin levels by c-mpl-mediated binding to platelets

Abstract: The involvement of platelets and the c-mpl receptor in the regulation of thrombopoietin (TPO) plasma concentrations and tissue mRNA levels was investigated in both normal mice and mice defective in c-mpl (c-mpl- /-). Although c-mpl-/- mice have fewer platelets and higher plasma TPO activity than normal mice, there was no increase in TPO mRNA levels as measured by an S1 nuclease protection assay. After the intravenous injection of 125I-TPO, specific uptake of radioactivity by the spleen and blood cells was pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
173
1
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(187 citation statements)
references
References 24 publications
11
173
1
2
Order By: Relevance
“…Under normal circumstances, TPO is produced constitutively in the liver and serum levels of circulating TPO are regulated by the mass of platelets and megakaryocytes that internalize (via TPO receptors) and degrade TPO. 11,12 In this study, we did not observe the usual inverse relationship between serum TPO and platelet count, 1,2 suggesting that decreased platelet mass (and thereby decreased TPO clearance) might not be responsible for the increase in serum TPO levels observed. Our study was not designed to measure TPO production, but an increase in TPO production could be derived either from hepatic or extrahepatic sources.…”
Section: Discussioncontrasting
confidence: 47%
“…Under normal circumstances, TPO is produced constitutively in the liver and serum levels of circulating TPO are regulated by the mass of platelets and megakaryocytes that internalize (via TPO receptors) and degrade TPO. 11,12 In this study, we did not observe the usual inverse relationship between serum TPO and platelet count, 1,2 suggesting that decreased platelet mass (and thereby decreased TPO clearance) might not be responsible for the increase in serum TPO levels observed. Our study was not designed to measure TPO production, but an increase in TPO production could be derived either from hepatic or extrahepatic sources.…”
Section: Discussioncontrasting
confidence: 47%
“…Since TPO appears to be an important regulator of platelet number, it is possible that abnormalities of TPO regulation may contribute to the pathogenesis of ET. Studies have shown that there is an inversely proportional relationship between circulating TPO levels and platelet/megakaryocyte mass through cytokine binding to receptor expressed on the surface of these cells (Fielder et al, 1996;Kuter & Rosenberg, 1995). However, although this relationship is generally maintained in thrombocytopenia and normal steady-state haemopoiesis, it does not appear to hold true in thrombocythaemic situations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between TPO concentrations and platelet counts in the thrombocytopenic patients was weak, suggesting that factors other than platelet mass also contribute to the regulation of circulating TPO levels (Fig 1). The circulating TPO level is probably regulated by platelet mass through TPO binding to c-mpl on platelets (Fielder et al, 1996). Since TPO promotes proliferation and maturation of megakaryocytes, megakaryocyte mass may also regulate the circulating TPO level, possibly through TPO binding to c-mpl on megakaryocytes.…”
Section: Discussionmentioning
confidence: 99%